Should the Cash Receipt System (CRS) be Implemented to Optimize Taxes in the Indonesian MSME Sector? - Adesurya, Rakib; Abbas, Yulianti (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to analyze the viability of applying a Cash Receipt System (CRS) concept in supervising tax revenue from the MSMEs sector to add the consideration for implementing CRS in Indonesia using the OECD (2015) framework. Design/methodology/approach: This study uses a descriptive qualitative approach in the form of a case study conducted at the Directorate General of Taxes (DGT). The study was carried out by analyzing literature analysis, analyzing taxation data on the MSMEs sector, and analyzing interview results. The data collection method consists of secondary data through literature analysis and primary data through interviews with respondents from the DGT, Regional Revenue Agency, taxpayers in the MSMEs sector, consultants, and related associations. Research Findings: Research shows that CRS policy does not fulfill some OECD (2015) principles, especially Neutrality, Efficiency, and Equity. This research emphasizes the importance of tax education and financial literacy in the MSME sector for Indonesia's sustainability of tax revenues. Theoretical Contribution/Originality: Suggested by the OECD (2017), the study contributes to the body of knowledge regarding the application of the fiscal device to counteract tax evasion in Indonesia. Keywords: Fiscal Device, Cash Receipt, Tax Evasion, MSME